أثر مهارات القيادة لدى رؤساء الأقسام على تفعيل الأداء الإداري من وجهة نظر جامعة محمد الشريف مساعدية – سوق أهراس - حكيمة بروك (My University, 2019)
Our study aimed at identifying the leadership skills of department heads to activate the administrative performance from the point of view of the heads of the department of the University of Mohamed Cherif Mesaadia Souk Ahras ,the questionnaire was used as a data collection tool based on the descriptive analytical approach ,where 30 questionnaires were distributed on a target sample represented by heads of departments of Mohamed Cherif Messaadia University,and all the distributed questionnaires were retrieved and analyzed using the program Spss,we came up with a set of results :  there is a positive relationship between the leadership skills of deparetement headsand the level of administrative performance from the point of view of depatement heads of university of Mohamed Cherif Mesaadia Souk Ahras  the absence of statistically significant differences in the attitudes of the heads of the department of the university of Mohamed Cherif Mesaadia in their response to the impact of leadership skills on administrative performance due to demographic variables. ......................................................... هدفت دراستنا للتعرف على مدى تأثير المهارات القيادية لدى رؤساء الأقسام على تفعيل الأداء الإداري من وجهة نظر رؤساء أقسام جامعة محمد الشريف مساعدية – سوق أهراس - ، وقد استخدمت الإستبيانة كأداة لجمع البيانات بالاعتماد على المنهج الوصفي التحليلي ، حيث تم توزيع 03 استبيان على عينة قصدية تمثلت في رؤساء أقسام جامعة محمد الشريف مساعدية ، و استرجعت كافة الاستبيانات الموزعة ، وقمنا بتحليلها باستخدام برنامج Spss ، و توصلنا إلى مجموعة من النتائج أهمها :  وجود علاقة ايجابية بين المهارات القيادية لدى رؤساء الأقسام و مستوى الأداء الإداري من وجهة نظر رؤساء أقسام جامعة محمد الشريف مساعدية –سوق أهراس-  عدم وجود فروق ذات دلالة إحصائية في اتجاهات رؤساء أقسام جامعة محمد الشريف مساعدية في استجاباتهم حول تأثير المها رات القيادية على الأداء الإداري تعود للمتغيرات الديموغرافية .